2004
DOI: 10.1207/s15327663jcp1404_8
|View full text |Cite
|
Sign up to set email alerts
|

Is the Implicit Association Test a Valid and Valuable Measure of Implicit Consumer Social Cognition?

Abstract: This article discusses the need for more satisfactory implicit measures in consumer psychology and assesses the theoretical foundations, validity, and value of the Implicit Association Test (IAT) as a measure of implicit consumer social cognition. Study 1 demonstrates the IAT's sen sitivity to explicit individual differences in brand attitudes, ownership, and usage frequency, and shows their correlations with IAT-based measures of implicit brand attitudes and brand re lationship strength. In Study 2, the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
231
1
27

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(264 citation statements)
references
References 97 publications
(153 reference statements)
5
231
1
27
Order By: Relevance
“…That is, the stronger the automatic associations between the self and female and the self and good, the stronger the automatic linkage between female and good. Also consistent with the implicit balance notion, subsequent work by Brunel, Tietje, and Greenwald (2004) revealed that Macintosh computer users showed stronger automatic evaluative associations for that brand relative to PC users, as revealed both in positivity and in self associations. Indeed, objects, products, and brands can be part of the self-concept and contribute to defining one's identity (e.g., Aaker, 1999;Belk, 1988;James, 1890;Kleine, Kleine, & Kernan, 1993;Wicklund & Gollwitzer, 1982).…”
Section: Study 3: Spreading Automatic Activation To the Selfsupporting
confidence: 60%
See 2 more Smart Citations
“…That is, the stronger the automatic associations between the self and female and the self and good, the stronger the automatic linkage between female and good. Also consistent with the implicit balance notion, subsequent work by Brunel, Tietje, and Greenwald (2004) revealed that Macintosh computer users showed stronger automatic evaluative associations for that brand relative to PC users, as revealed both in positivity and in self associations. Indeed, objects, products, and brands can be part of the self-concept and contribute to defining one's identity (e.g., Aaker, 1999;Belk, 1988;James, 1890;Kleine, Kleine, & Kernan, 1993;Wicklund & Gollwitzer, 1982).…”
Section: Study 3: Spreading Automatic Activation To the Selfsupporting
confidence: 60%
“…Applying the implicit balance notion to the consumer domain, Brunel, Tietje, and Greenwald (2004) found that Macintosh users show more positive automatic evaluative associations for that brand relative to PC users. The present research has several advances over previous work on implicit balance.…”
Section: Implications For Implicit Balancementioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these cognitions can have a strong impact on physiological responses [35] and behavior [36]. Measures of implicit cognition aim to provide an index of an attitude or cognition without requiring a participant's awareness or conscious access to the attribute under investigation [37,38]. This is achieved through tasks where participants respond in an "automatic manner" (p. 347 [39]), with little or no opportunity for attentional con-trollability or self-monitoring [19,40,41].…”
Section: Implicit Cognition and Measurementmentioning
confidence: 99%
“…We suggest that the results may reflect an implicit preference for the companion in people without explicit recognition and utilization of companion resources. Many previous IAT studies showed implicit attitudinal preference in consumer behavior (Brunel, Tietje, & Greenwald, 2004), prejudice (Dasgupta & Greenwald, 2001;Dasgupta et al, 2000;Greenwald et al, 1998), and voting behavior (Arcuri, Castelli, Galdi, Zogmaister, & Amadori, 2008) independent of explicit attitudes. Similar to these previous findings, in our experiment, participants who do not have companions would have implicit attitudinal preference or desire for a companion.…”
Section: Discussionmentioning
confidence: 94%